Teodisi Islam dan Masalah Kejahatan: Suatu Analisis Konseptual - Nurhanisah Senin; Mustafa Kamal Amat Misra; Nazneen Ismail; Marina Munira Abdul Mutalib; Wan Mohd Fazrul Azdi Wan Razali; Mohd Hamidi Ismail; Siti Dayana Nu’man Zainudin (Nun Gemilang Ent, 2026)
Indexed by MyCite